2014
DOI: 10.3109/10717544.2013.878857
|View full text |Cite
|
Sign up to set email alerts
|

Nose to brain microemulsion-based drug delivery system of rivastigmine: formulation and ex-vivo characterization

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder leading to irreversible loss of neurons, cognition and formation of abnormal protein aggregates. Rivastigmine, a reversible cholinesterase inhibitor used for the treatment of AD, undergoes extensive first-pass metabolism, thus limiting its absolute bioavailability to only 36% after 3-mg dose. Due to extreme aqueous solubility, rivastigmine shows poor penetration and lesser concentration in the brain thus requiring frequent oral dosing. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…Another method for the treatment of AD is by delivering drugs than can prevent the metabolism of certain enzymes in the brain. For example, rivastigmine hydrogen tartrate (RT) is a therapeutic drug which is a carbamate derivative and it reversibly prevents the metabolism of aceylcholinesterase (AChE) and butyrylcholinesterase (BChE) in the CNS . However, the delivery of RT to the brain is very challenging as it restricts permit to the brain due to its hydrophilic nature, requires repeated dosing, and causes serious cholinergic side effects such as bradycardia, anorexia, dyspepsia etc .…”
Section: Applications Of Msnsmentioning
confidence: 99%
“…Another method for the treatment of AD is by delivering drugs than can prevent the metabolism of certain enzymes in the brain. For example, rivastigmine hydrogen tartrate (RT) is a therapeutic drug which is a carbamate derivative and it reversibly prevents the metabolism of aceylcholinesterase (AChE) and butyrylcholinesterase (BChE) in the CNS . However, the delivery of RT to the brain is very challenging as it restricts permit to the brain due to its hydrophilic nature, requires repeated dosing, and causes serious cholinergic side effects such as bradycardia, anorexia, dyspepsia etc .…”
Section: Applications Of Msnsmentioning
confidence: 99%
“…Indeed, some current therapeutic approaches include reversible cholinesterase inhibitor like rivastigmine. 2 Epidemiological studies have important contributions to presenting new bases for future. For instance, risks of developing Alzheimer's disease can be decreased by smoking tobacco and it was suggested that nicotine inhibits neuronal apoptosis which prevents the Ab25-35-induced neurotoxicity 15 pointing a starting point to new therapeutic approaches.…”
Section: Selected Therapeutic Advancesmentioning
confidence: 99%
“…The mucosa must be oriented with the mucosal side facing the donor chamber. The thickness of the tissue (usually 200 µm) should be measured and mentioned as it is directly linked to the diffusion rate (Tas et al, 2009;Shah et al, 2015;Acharya et al, 2013). The influence of the thickness was investigated in a study that compared the permeation of both hydrophilic (i.e.…”
Section: Ex-vivo Modelsmentioning
confidence: 99%